Three Women with Non-Segmental Vitiligo in Three Generations of a Family: A Case Report - Fatemeh Chorli; Zahra Ghodsalavi; Maryam Hajilari; Farzad Dastaviz; Majid Mehri; Morteza Oladnabi (Golestan University Of Medical Sciences, 2018)
Background: Vitiligo is a common autoimmune skin disorder, which is characterized by incomplete penetrance and genetic heterogeneity. It is classified into two types: segmental and non-segmental, and most cases suffer from non-segmental vitiligo. The disease affects about 2-10 in 1000 people in different population with no sex predilection. Furthermore, the genetics of vitiligo cannot be described by Mendelian pattern of inheritance. We herein report three female relatives (niece, aunt, grandmother) with non-segmental vitiligo in a family. Case description: The symptoms and severity of the disease varied between the cases. Incomplete penetrance was completely evident in this family. The grandmother had not received any treatment, but the aunt and niece were receiving medication and phototherapy. However, these treatments were not beneficial for them. Conclusion: Currently there is no effective treatment or screening method for vitiligo. Thus, genetic counseling, risk determination and identification of other genetic contributors could be beneficial.